The cholesterol metabolite 27-hydroxycholesterol inhibits SARS-CoV-2 and is markedly decreased in COVID-19 patients (2020)
There is an urgent need to identify antivirals against the coronavirus SARS-CoV-2 in the current COVID-19 pandemic and to contain future similar emergencies early on. Specific side-chain cholesterol oxidation products of the oxysterols family have been shown to inhibit a large variety of both enveloped and non-enveloped human viral pathogens. Here we report on the in vitro inhibitory activity of the redox active oxysterol 27-hydroxycholesterol against SARS-CoV-2 and against one of the common cold agents HCoV-OC43 human coronavirus without significant cytotoxicity. Interestingly, physiological serum levels of 27-hydroxycholesterol in SARS-CoV2 positive subjects were significantly decreased compared to the matched control group, reaching a marked 50% reduction in severe COVID-19 cases. Moreover, no correlation at all was observed between 24-hydroxycholesterol and 25-hydroxycholesterol serum levels and the severity of the disease. Opposite to that of 27-hydroxycholesterol was the behaviour of two recognized markers of redox imbalance, i.e. 7-ketocholesterol and 7βhydroxycholesterol, whose serum levels were significantly increased especially in severe COVID-19. The exogenous administration of 27-hydroxycholesterol may represent in the near future a valid antiviral strategy in the worsening of diseases caused by present and emerging coronaviruses.